PERSEPSI PEMUDA TERHADAP USAHA PERIKANAN TANGKAP DI DESA API-API KABUPATEN PEKALONGAN - , YOGI ARIADENTA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to determine the perceptions of youth, youth interests, and expectations of youth to the fisheries sector, and identify factors - factors that influence it. The study was conducted in October 2012 to December 2012, with the method of survey methods in Api-Api Village, Sub-District Wonokerto, District Pekalongan. Youth respondents aged between 18-30 years, were divided into five criteria, namely the criteria of respondents who are currently school and comes from a family of fishermen, the group of respondents who are not in school and comes from a family of fishermen, the group of respondents who are currently school but not from from a family of fishermen, the group of respondents who are not in school and not come from a family of fishermen, as well as the group of respondents who are currently working as a fisherman. The results showed that youths in Api-Api Village still perceive work as a fisherman saturating jobs (13.70%), rundown (12.59%), drunk (11.85%), and dangerous (11.11%), but it does not reduce the interest of the young man to work as a fisherman. That is because the average - average people have no other choice but to work as a fisherman. Expectations of youth to the fisheries sector is still very high, young people still have high hopes for the fisheries sector in their village for the sector could become the foundation of the family economy. Factors - factors that influence youth perceptions of the fisheries sector is the experience factor and family factors.